Assessment of Natural Radioactivity and Radiological Hazard in Soil Samples of the Most Popular Tourist Place in Babylon, Iraq - Inaam H. Kadim (Journal of Global Pharma Technology, 2018)
In the present investigation, the activity concentrations of 238U, 232Th and 40K in soil samples collected from the most popular tourist place in Babylon, Iraq are determined using gamma ray spectroscopy. The measured activity concentration ranges from 5.8 to 30.4 Bq kg-1 with an average value of 14.92 Bq kg-1 and 2.9 to 45.39 Bq kg-1 with an average value of 24.7 Bq kg-1 and 110.6 to 369.9 Bq kg-1 with an average value of 285.13 Bq kg-1, for 238U, 232Th and 40K, respectively. The radium equivalent activity ranges from 19.06 to 85.64, which is lower than the safe limit 370 Bq kg-1 as set by the Organization for Economic Cooperation and Development. The absorbed dose of all the investigated samples varies from 10.32 to 40.03 nGyh-1.The annual effective dose equivalent ranges from 0.04 to 0.047 mSv. The values of internal and external hazard index of all the samples ranges from 0.3 to 0.1, and 0.08 to 0.26 45 respectively. It is observed that the soil of tourist place in Babylon is suitable for construction purpose without posing any health hazard.Keywords: NaI Tl) detector, Natural radioactivity, Annual Effective Dose, Soil samples.